Programa Indaga Kids, basado en el ABP, para desarrollar la actitud científica en estudiantes de sexto grado de una Institución Educativa - Alto Trujillo, 2018 - Cruz Pérez, Eri Luzvani (2019)
The present titled investigation: “Program Indaga Kids, once the ABP was based on, in order to develop the scientific attitude in students of sixth degree of an Educational Institution – Alto Trujillo, 2018 ”, he aimed at determining in what measure the application of the program Indaga Kids, once the ABP was based on, the N develops the scientific attitude in students of sixth degree of primary school of the Educational Institution significantly 82105 Solaris – Alto Trujillo, 2018._x000D_ Investigation is applied designing quasi experimental, with Pre and Post Test, with experimental group and control, the aforementioned investigation was accomplished with 52 students' sample of the sixth one the Educational Institution's degree of primary education N 82105 Solaris – Alto Trujillo._x000D_ Results evidence than the application of the program Indaga Kids develops significantly the scientific attitude in students of sixth degree of primary school of the Educational Institution N 82105 Solaris – Alto Trujillo, 2018.